2017
DOI: 10.1039/c7an00902j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the metabolism of the anticancer drug Triapine: electrochemical oxidation, microsomal incubation and in vivo analysis using LC-HRMS

Abstract: α-N-Heterocyclic thiosemicarbazones are among the most promising ribonucleotide reductase inhibitors identified so far. Triapine, the most prominent representative of this class of substances, has been investigated in multiple phase I and II clinical trials. With regard to clinical practice, Triapine showed activity against hematological diseases, but ineffectiveness against a variety of solid tumors. However, the reasons are still vague and the amount of ADME (absorption, distribution, metabolism and excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…administration [ 15 ], as well as very briefly its metabolism and excretion via acetylation and hydroxylation [ 16 ]. In line with these reports, our investigations on Triapine in mice showed also a short plasma half-life time and fast excretion [ 17 , 18 ]. Furthermore, we recently studied the metabolic pathways of Triapine by the application of different analytical tools, including electrochemical oxidation, microsomal incubation and in vivo experiments [ 18 ].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…administration [ 15 ], as well as very briefly its metabolism and excretion via acetylation and hydroxylation [ 16 ]. In line with these reports, our investigations on Triapine in mice showed also a short plasma half-life time and fast excretion [ 17 , 18 ]. Furthermore, we recently studied the metabolic pathways of Triapine by the application of different analytical tools, including electrochemical oxidation, microsomal incubation and in vivo experiments [ 18 ].…”
Section: Introductionsupporting
confidence: 79%
“…In line with these reports, our investigations on Triapine in mice showed also a short plasma half-life time and fast excretion [ 17 , 18 ]. Furthermore, we recently studied the metabolic pathways of Triapine by the application of different analytical tools, including electrochemical oxidation, microsomal incubation and in vivo experiments [ 18 ]. The data showed that the key metabolites of Triapine are (1) the dehydrogenated ring-closed thiadiazole (M1, Scheme 1 ), which lost the crucial chemical property of anticancer α- N -heterocyclic thiosemicarbazones to coordinate biologically relevant metal ions and showed no cytotoxic activity and (2) different hydroxylated species (M2–M4, Scheme 1 ) [ 18 ].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The reasons for this inefficacy of Triapine monotherapy against solid tumors are still not fully understood. Probable explanations (discussed in more detail below) include inappropriate drug delivery due to the very short plasma half-life (47,132,143), fast metabolism/excretion (142) and/or rapid development of drug resistance (127). Despite these drawbacks, thiosemicarbazones have remained the focus of interest.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Additionally, αmangostin and other cytotoxic drugs generally have limitations that influence their effectiveness, including a first fast metabolism reaction, an efflux reaction induced by transporter intercellular, fast drug release and a non-specific target site. [22][23][24] Drug bioavailability is an important parameter to determine how successful the drug molecules pass through in pharmacological phases such as biopharmaceutics, pharmacokinetics, and pharmacodynamics. 25 To achieve the maximum bioavailability, drug solubility is one of the primary factors that can increase the drug bioavailability.…”
Section: Introductionmentioning
confidence: 99%